Term premium dynamics and its determinants: The Mexican case - Ana Aguilar-Argaez; María Diego-Fernández; Rocío Elizondo; Jessica Roldán-Pe\~na (Banco de México, 2020)
We estimate the term premium implicit in 10-year Mexican government bonds from 2004 to 2019, and analyze the main determinants explaining its dynamics. To do so, we decompose the longterm interest rate into its two components: the expected short-term interest rate and the term premium. The results show that the Mexican term premium increased significantly during three episodes: i) the global financial crisis; ii) the "Taper Tantrum"; and iii) the U.S. presidential election of 2016. In contrast, the term premium decreased, to historically low levels, during the U.S. "Quantitative Easing" and the "Operation Twist" programs. Additionally, we find that the main determinants that explain the dynamics of the premium are the compensation for FX risk (as a proxy of inflationary risk premium), the real compensation, and the U.S. term premium.
Keywords: G12; E43; C12; C53; 330; Term premium; expected short-term interest rate; affine model